Impact of Saccharomyces boulardii on jaundice in premature infants undergoing phototherapy - Di Hu; Ying Wang; Suyan Yang; Huijuan Zhang (Elsevier, 2023)
Objectives: To evaluate the therapeutic effect of Saccharomyces boulardii supplementation on jaundice in premature infants undergoing phototherapy. Methods: In this article, the authors reviewed 100 hospitalized jaundiced premature infants under 35 weeks of gestational age. All infants were assigned to a control group (n = 45) and a treatment group (n = 55) randomly. The infants in the treatment group received S. boulardii supplementation by undergoing phototherapy and the infants in the control group were only treated by phototherapy. The total serum bilirubin levels were detected before and at the end of phototherapy, and transcutaneous bilirubin levels were measured on the 1st, 4th, 8th and 15th day of treatment. The duration of jaundice resolution and phototherapy, stool frequency, and characteristics were compared after phototherapy. Results: The duration of jaundice resolution and phototherapy were shortened. Total serum bilirubin level was lower than the control group at the end of phototherapy (p < 0.05). Transcutaneous bilirubin levels decreased more significantly on the 8th and 15th day of treatment (p < 0.05), while there were no significant differences on the post-treatment 1st and 4th day (p > 0.05). In addition, bowel movements including stool frequency and Bristol Stool Form Scale ratings of stools also improved after treatment. Conclusions: S. boulardii in combination with phototherapy is effective and safe in reducing bilirubin levels and duration of phototherapy, accelerating jaundice resolution in premature infants with jaundice. The procedure also provided an ideal therapeutic effect of diarrhea induced by phototherapy to promote compliance and maternal-infant bonding.